1983
DOI: 10.1126/science.219.4588.1065
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Molecular Sieve 4A: Anomalous Compressibility and Volume Discontinuities at High Pressure

Abstract: Unit cell parameters of synthetic zeolite 4A were measured at several pressures to 40 kilobars with both water and an alcohol mixture as hydrostatic pressure media. Compression in water was normal, with no observed phase transitions. Compression in alcohols was twice as great as in water, and three volume discontinuities were observed. These volume changes in alcohol were rapid with increasing pressure but sluggish in reverse. High-pressure "phases," all of which are dimensionally cubic, are progressively more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 3 publications
2
67
0
1
Order By: Relevance
“…zeolite Na-A, Hazen, 1983;Hazen and Finger, 1984). The first structure-refinements that showed, unambiguously, the P-induced ''overhydration effect'' in natrolite and ''natrolite-like'' materials (i.e.…”
Section: In Situ High-pressure Experiments On Zeolites: Technical Aspmentioning
confidence: 99%
See 1 more Smart Citation
“…zeolite Na-A, Hazen, 1983;Hazen and Finger, 1984). The first structure-refinements that showed, unambiguously, the P-induced ''overhydration effect'' in natrolite and ''natrolite-like'' materials (i.e.…”
Section: In Situ High-pressure Experiments On Zeolites: Technical Aspmentioning
confidence: 99%
“…Its framework shows strong structural homologies with that of sodalite. The elastic behaviour of this zeolite was first studied by Hazen (1983) and Hazen and Finger (1984) by in situ single-crystal diffraction up to 4 GPa using both penetrating and non-penetrating P-media. The authors observed a significantly different compressional behaviour of this zeolite in response to the molecular size of the P-transmitting medium: the compressibility was higher when non-penetrating P-media were used.…”
Section: Group 4: Zeolites With Six-membered Ringsmentioning
confidence: 99%
“…This occurs due to distortion of polyhedral network without bond breaking but only altering their bond angles with greater change in large cation cavity [14]. Compounds with such polyhedral links including silica polymorphs [15][16][17][18], LiCsSO 4 [19], NaTiPO 5 and related compounds [20,21], perovskites [22][23][24], feldspars [25], zeolites [26][27][28] have been extensively studied experimentally to understand their structural behavior at high pressures. For example, the principal compression mechanism in the structure of KTiPO 5 with corner linked TiO 6 octahedra and PO 4 tetrahedra under pressure are changes in polyhedral angles and coordination environment of K atom [29].…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of these confined species, coupled with the confinement geometry, play an important role in determining catalytic, ion exchange and molecular sieving properties [1]. To alter the chemistry and geometry of a given framework, cation substitution and temperature effect have been applied extensively [2][3][4][5], while pressure effect has been limited to measuring compressibilities and investigating structural amorphizations [6,7]. Recently, however, interests in exploring the high pressure chemistry of zeolites have expanded in both experimental and theoretical studies and demonstrated how a zeolitic framework responds to applied hydrostatic pressure and how this can regulate the zeolitic water content, cation distribution, and selectivity toward foreign species [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%